Utilization of pangas protein isolates and by‐products in fish sausages: Effect on quality attributes and acceptability. Issue 8 (20th June 2022) - Surasani, Vijay Kumar Reddy; Mandal, Amit; Sofi, Faisal Rashid; Joshi, Sagar
Abstract: Aim of the study was to aid the utilization of pangas protein isolates (PPI) and pangas processing by‐products (PPB) in food products (rohu mince sausage) and to evaluate the quality of the developed products. Rohu mince in sausages was replaced with PPI and PPB at 0, 2.5, 5.0, and 10% levels and the composition, physical, textural, and sensorial quality of sausages were assessed. Increasing PPI and PPB content in sausages increased its crude protein and lipid content ( p  < .05); however, the expressible moisture of sausages decreased with increasing levels of PPI ( p  < .05). Increasing PPB and PPI content in sausages showed a negative impact on its gel strength, while the differences in the color, textural, sensory attributes and acceptability of sausages were insignificant. Results indicated that the PPI and PPB from pangas could be successfully incorporated into fish sausages without significantly affecting the quality and acceptability. Novelty impact statement: In this study, pangas fish processing by‐products (PPB) and protein isolates (PPI) were used to supplement fish sausages with an aim of its utilization in food systems. Adding PPB and PPI to sausages influenced its physicochemical attributes without significantly causing changes in its eating quality, opening a new way to utilize these raw materials in food industry. Using PPI and PPB, edible fish meat sausages with good acceptability could be developed.